Analysis of Student Errors in Solving Mathematics Problems at Muhammadiyah Senior High School Special Program of Kottabarat Surakarta City - Ratna Herawati; Ismiyati Marfuah (Mathematics Education Study Program, 2021)
Learning mathematics is a crucial part of education. Mathematics is one of the subjects feared by students. One of the problems in the object of mathematics study is the material for X class of Senior High School. Students of grade X are undergoing adaptation from the junior high school level to the high school level so that the findings of conceptual errors, calculations, and thinking patterns in problem-solving algorithms are often found. This also happened to the students of the Muhammadiyah Senior High School Special Program of Kottabarat Surakarta. In connection with the above problems, the author analyzes student errors in solving math problems at the Muhammadiyah senior high school special program of Kottabarat Surakarta.This study aims to find out errors, causes of error, and alternative problem solving related to students' errors in solving math problems. This research is qualitative descriptive research. The research subjects were taken by sampling purposes. they are three students of class X. The research method used is qualitative research methods, data collection techniques used in this study are test methods, interview methods, and documentation methods. The research instrument is the main instrument, namely the researcher himself and the auxiliary instruments in the form of test sheets, interview guidelines, and field notes. The data analysis technique uses data reduction, data presentation, and data verification, and triangulation techniques. The results of this study indicate that the types of errors that did most often made are errors in understanding questions that were 9 times, process skills errors and coding errors were 6 times, and reading errors were never made by research subjects.